AUDITOR’S ABILITY DETECT FRAUD: EXPERIENCE, PROFESSIONAL SKEPTICISM, TIME PRESSURE, COMPETENCE - Wahyudi, Wahyudi; Haliah, Haliah; Nirwana, Nirwana; Yulitasari, Yulitasari (Penelitian dan Pengembangan Ilmu, 2025)
This research explores how professional skepticism, time pressure, and competence influence auditors’ effectiveness in detecting fraud, with experience functioning as a moderating variable. The study targeted 119 auditors from the Inspectorate Office in the Luwu Raya region, from which 104 were selected using purposive sampling based on specific criteria. Hypothesis testing was conducted through Multiple Regression Analysis and Moderated Regression Analysis (MRA). The results indicate that both professional skepticism and competence positively and significantly impact auditors’ fraud detection capabilities. Conversely, time pressure does not exhibit a significant effect. Furthermore, experience moderates the relationships between professional skepticism, time pressure, and competence with fraud detection ability, acting as a strengthening factor. This suggests that auditors with greater experience are better positioned to apply their skepticism, manage time-related challenges, and utilize their competence effectively in uncovering fraud. The study contributes to the existing literature by presenting a framework that highlights the interrelation of these factors in fraud detection, while also supporting attribution theory by emphasizing the role of professional traits and experience in enhancing audit performance